Building a case against strategic equifinality: Hybrid ideal type service organizations in a developing country. Issue 6 (8th July 2014) - Madanoglu, Melih; Okumus, Fevzi; Avci, Umut
Abstract : Purpose: – The purpose of this paper is to build a case against strategic equifinality. This is accomplished by employing hybrid ideal types approach and testing the effect of these strategic types on firm performance among service firms in the context of a developing country. Design/methodology/approach: – Data were collected via a self-administered survey. The final sample of this study encompassed 169 ideal type hybrid companies operating in the tourism industry in Mugla, Turkey. Findings: – The research findings indicate that prospectors and hybrid prospector-analyzer (PA) orientations outperform defenders based on several financial and non-financial performance measures. However, all other strategic orientations show identical performance. Research limitations/implications: – The research findings imply that adopting a hybrid strategy is a viable option. In addition, SMEs in developing countries should exercise some caution when deciding to adopt a defender strategy. Originality/value: – This study uses hybrid ideal types for service firms in a dynamic business environment in a developing country.